Determinan Ekspor Besi dan Baja Indonesia - Inas Zafirah Mahardika; Siti Aisyah (Ekonomis: Journal of Economics and Business, 2023)
Exports are a means for each country to increase the country's revenue post. Countries around the world will strive to specialize in a particular product for a commodity in order for the product to be in demand in the International market. Iron and steel is one of Indonesia's leading export products and is one of the industries that drives the wheels of the national economy. Various macroeconomic variables will have an impact on national iron and steel production and the export volume of these commodities. This study uses the Error Corection Model (ECM) analysis in testing the effect of Gross Domestic Product (GDP), exchange rate, and inflation rate on Indonesia's iron and steel exports during the 1990-2020 period. The results of the regression analysis stated that in the short term, the rupiah exchange rate negatively affects the value of iron and steel exports, while GDP and inflation do not affect the value of iron and steel exports. Meanwhile, in the long run, GDP has a positive effect on the value of iron and steel exports and inflation negatively affects the value of iron and steel exports, while the exchange rate does not affect the value of iron and steel exports. Based on these results, the government is expected to maintain national monetary stability and control the inflation rate so that the rupiah exchange rate does not fluctuate too sharply and keep the economy growing. Where these conditions will attract investors, especially in the national iron and steel industry sector of Indonesia.